A Comprehensive Review of the Development Characteristics and Future Trends of TOD in Chinese Urban Rail Transit - Linyan Wang; Haishan Xia (Urban Rail Transit)
Abstract The transit-oriented development (TOD) concept has become a significant catalyst for urban development in China, which has undergone rapid urbanization and has actively participated in the development of public transportation networks over the past 20 years. TOD not only guides the transformation of transportation modes but also leads the development of urban spaces. The extensive construction of urban rail transit in China highlights the universal patterns of TOD and reflects the uniqueness of Chinese practices. This paper analyzes the characteristics of urban development and TOD in developed countries, summarizing the common laws driving TOD in theoretical research. It then compares China, which is in a period of rapid rail transit construction, to identify the unique developmental laws of transit-oriented development of rail transit in China (TOD-RTC). The paper further examines the developmental characteristics of TOD-RTC in practice, considering both temporal and spatial aspects, and explores the reasons behind the formation of individual differences in TOD-RTC. Finally, it discusses the new value and potential that TOD brings to urban development, along with predicting future development trends.